(3Yde faS Gdfeh (B:s (3GdWahdI hGdeQGgbI (B/s - (3GdQjeGhj, eMeO YhOIs ((3YeGf, GdCQOf (B:s (3OGQ GdeSjQI ddfTQ hGdJhRjY hGdWHGYI,s, 2003)
(3jJfGhd GdcJGH cd eG jNU GdWahdI(B.s
(3HHdjhLQGajI (B: (3U(B. 332-334.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
(3GdYRQj(B.s
Keywords: (3Yde GdfaS GdGQJbGFjs; (3GdCWaGds -- (3fehs; (3GdeQGgbIs -- (3LhGfH faSjIs; (3GdCWaGds -- (3Yde faSs; (3GdeQGgbhfs -- (3Yde faSs